PERAN ETIKA ADMINISTRASI PUBLIK DALAM MEWUJUDKAN GOOD GOVERNANCE - R. Moch. Agus Ramdhan; Aang Rahmatulloh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Governance practices in Indonesia continue to face challenges characterized by weak bureaucratic integrity, abuse of authority, and the limited implementation of good governance principles. These issues indicate that bureaucratic problems are not merely structural and administrative in nature but are also closely linked to ethical dimensions in public service delivery. This study aims to analyze the role of public administration ethics in fostering good governance. The research employs a qualitative approach using a literature review method by examining public administration theories, regulatory frameworks, and relevant scholarly articles. The findings demonstrate that public administration ethics serve as both a normative foundation and a behavioral control mechanism in promoting transparency, accountability, professionalism, and the rule of law. Strengthening the values of integrity, responsibility, and public service orientation contributes to the development of a citizen-centered organizational culture. The implications suggest that integrating ethical systems into bureaucratic reform strategies is essential for achieving effective, participatory, and sustainable governance.